The Evaluation of human papillomavirus vaccination coverage for school aged girls in Badung District, Bali, Indonesia, 2016 – 2018 - Yuliyatni, Putu Cintya Denny; Sawitri, Anak Agung Sagung; I Gusti Agung Alit Naya; Mego Windyningtyas; Ni Kade Erveni; I Nyoman Sutarsa (Public Health and Preventive Medicine Archive, 2024)
Background and purpose: Since 2016, Badung District, Bali has implemented a free HPV vaccination program for school children, with vaccination coverage reported to be over 90% in 2016-2018. This study aims to objectively assess the coverage of HPV vaccination among school children in Badung District. Methods: This survey used a cross-sectional design that conducted between March and June 2019. Sample selection was done by systematic random sampling, following the WHO guidelines. A total of 216 families met the sample criteria, with a total of 249 children from all families. Respondents in this study were eligible girls' mothers or families who knew the child's vaccination history. Variables of this study were sociodemographic characteristics of respondents and children, HPV vaccination recall and HPV child vaccination validation. The data collected were analyzed descriptively to calculate the coverage of recall and validation of HPV vaccination. Results: The majority of respondents were mothers (70.83%) with a high school education (51.85%). The median age was 43 years (IQR=8 years). Each family had a mean of 1.15 eligible children (SD=0.39). Of the 249 children, most were aged 16-19 years (43.37%), with age at vaccination mostly ≤12 years (46.52%). HPV vaccination coverage by recall was 82.32% (95%CI: 77.56-87.09), with HPV vaccination coverage by validation was 76.59% (95%CI: 70.74-82.43). Conclusion: After validation, vaccination coverage was lower than vaccination coverage by recall. The health office needs to improve the vaccination registration system, in particular the uniformity of registration and record keeping to ensure proper traceability of vaccination history.